A Review on Indoor Air Quality Monitoring using IoT at Campus Environment - Ananda Hapsari, Anindya; Iqbal Hajamydeen, Asif; Irsyad Abdullah, Muhammad I (International Journal of Engineering and Technology, 2018)
Indoor Air Quality (IAQ) systems provide a feasible way to maintain a healthy environment. The purpose of this study is to investigate IAQ monitoring systems, summarize existing studies, and to recommend research on IAQ monitoring that using the Internet of Things (IoT). In this systematic review the author analyzes and summarizes articles about IAQ using IoT, obtained from three databases. Based on the criteria, there were 36 studies selected that discusses IAQ, 24 are system development, six are evaluation and comparative articles, three studies proposes methods, and the other three are review articles. From the articles, there are only six researchers have conducted research on campus environment. The relevant past research was reviewed and provided discussion material on monitoring systems, sensors, devices used, and Internet of Things for Indoor Air Quality.Â Â